Macroeconomic effects of terms of trade fluctuations in commodity exporting advanced economies. Issue 19 (20th April 2016) - Makin, Anthony J.; Rohde, Nicholas
ABSTRACT: The paper examines the impact of world commodity prices on national output and trade balances in Australia, Canada, New Zealand, and Norway, OECD economies that, unlike other advanced economies, are heavily dependent on commodity exports. Contrary to Dutch disease theory based on real exchange rate adjustment, it highlights the relative price effects of terms of trade (ToT) changes on gross domestic product and net exports with reference to the experience of this unique set of OECD countries. The econometric analysis verifies key predictions of this alternative perspective that ToT fluctuations should (i) have no significant short-run impact on GDP and that (ii) due to relative price effects a strong positive relationship between the ToT and net exports is unlikely.